PENYISIHAN ORGANIK LIMBAH CAIR DOMESTIK PADA INSTALASI PENGOLAHAN DENGAN SISTEM JOHKASOU KASUS: RUSUN DUKUH SEMAR, CIREBON - Prayatni Soewondo (Purifikasi, 2007)
Johkasou wastewater treatment system, which was developed in Japan, has been adapted in the Dukuh Semar low cost appartment in Cirebon City. Information on the community attitude in handling the sanitation problems was identified by questionairres. Whereas, the performance of the Johkasou instalation is evaluated according to Water Quality Standards according to goverment regulations No. 82/2001. Field observations showed that the organic removal rate reaches 88,94% on BOD and 84,66% on COD. While the instalation has an influent of about 1,1016 kg/day and an organic loading of about 0,0286 kg/m3/day. The rasio of BOD5/COD of the wastewater of the Johkasou instalation is 0,62. The efficiency of nitrogen removal reaches 80,85% for amonia with a loading of 0,852 kg/day and 52,69% for nitrate with a loading of 0,2644 kg/day. Other parameters that have also been observed are suspended solid (74,72%), fosfate (88,43%) and bacteria (99,63% as coliform). The quality of waste water that has not achieved the ideal standard is nitrogen, so there are needs to be further processing that includes nitrification and denitrification. The work applied by this instalation has not achieved its optimum capacity because of certain phisical conditions and also some imperfection in the instalation effected by the habitual conditions of the society living inside the housing area.